2016
DOI: 10.1016/j.orggeochem.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative estimates of paleo Arctic sea ice concentration based on source-specific highly branched isoprenoid alkenes: A further development of the PIP25 index

Abstract: Semi-quantitative estimates of paleo Arctic sea ice concentration based on source-specific highly branched isoprenoid alkenes: A further development of the PIP25 index Smik, L Please cite this article as: Smik, L., Cabedo-Sanz, P., Belt, S.T., Semi-quantitative estimates of paleo Arctic sea ice concentration based on source-specific highly branched isoprenoid alkenes: a further development of the PIP 25 index, Organic Geochemistry (2015), doi: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(164 citation statements)
references
References 31 publications
12
152
0
Order By: Relevance
“…It has been suggested that HBI III-producing diatoms bloom in higher abundance in open-water areas near the sea ice edge (Belt et al 2015; Smik et al 2016) due to enhanced mixing and nutrient availability at the surface. Although turbidity and dissolved silica availability are certainly important factors shaping the distribution of HBI III in zone B, the proximity of the ice edge in mid-July in this area is noteworthy, as this is a stable feature of the annual sea ice evolution in the fjord (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that HBI III-producing diatoms bloom in higher abundance in open-water areas near the sea ice edge (Belt et al 2015; Smik et al 2016) due to enhanced mixing and nutrient availability at the surface. Although turbidity and dissolved silica availability are certainly important factors shaping the distribution of HBI III in zone B, the proximity of the ice edge in mid-July in this area is noteworthy, as this is a stable feature of the annual sea ice evolution in the fjord (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Massé et al 2008; Müller et al 2012; Belt et al 2015), although reports of IP 25 in Arctic fjords are rare (Cabedo-Sanz et al 2013; Brown et al 2015). It has been suggested that more detailed interpretations of the past sea ice conditions can be obtained through the comparison between IP 25 and a related lipid biomarker (HBI III), which is likely produced by diatoms blooming in the open-water environment of the marginal ice zone (Belt et al 2015; Smik et al 2016). As such, the relative contributions to the sediment of endemic sea ice versus ice-edge phytoplankton can provide insights into past sea ice dynamics, and seasonal sea ice evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For more semi‐quantitative estimates of present and past sea ice coverage, Müller et al () combined the sea‐ice proxy IP 25 and phytoplankton biomarkers in a phytoplankton‐IP 25 index, the so‐called ‘PIP 25 index’: PIP25=[normalInormalP25]/([normalInormalP25]+([phytoplankton marker]×c)) with c is the mean IP 25 concentration/mean phytoplankton biomarker concentration for a specific data set or core. As phytoplankton biomarkers, we have used brassicasterol and dinosterol (for further discussion of advantages and limitations of the PIP 25 approach see Stein et al , ; Belt and Müller, ; Xiao et al , ; Smik et al , ). Following Müller et al 's () classification scheme, PIP 25 values between 0.3 and 0.5, 0.5 and 0.7, and »0.7 point to a reduced sea ice cover, a seasonal sea ice cover including an ice edge situation, and an extended to perennial sea ice cover, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As phytoplankton biomarker, brassicasterol was used (for further discussion of advantages and limitations of the PIP 25 approach see Belt and Müller, 2013;Smik et al, 2016;Stein et al, 2012;Xiao et al, 2015). Following the classification scheme of Müller et al (2011), PIP 25 values between 0.3 and 0.5, between 0.5 and 0.7, and 0.7 point to a reduced sea ice cover, a seasonal sea ice cover including an ice edge situation and an extended to perennial sea ice cover, respectively.…”
Section: Bartels Et Al: Atlantic Water Advection Vs Glacier Dynammentioning
confidence: 99%